MANAJEMEN KEUANGAN DAERAH : OPTIMALISASI PENGELOLAAN DANA ALOKASI UMUM (DAU) BAGI PEMBANGUNAN DAERAH - Isti'anah Isti'anah (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2009)
The implementation of fiscal balance policy is done through budget allocation for local governments, include balance fund. Furthermore, the policy has also been meant to reduce imbalance fund resources between central and local governments and to minimize fiscal gap among local governments as well. The general allocation fund (DAU) is allocated with aim to even distribution of financial capability interregional. The allocation is to finance local governments' need regarding implementation of decentralization system. The use fund is adjusted to priority and need each local government (block grant)